Cone beam computed tomographic evaluation of pharyngeal airway in North Indian children with different skeletal patterns - Kochhar, Anuraj Singh (World J Radiol, 2021)
BACKGROUND: In growing patients with skeletal discrepancies, early assessment of functional factors can be vital for the restoration of normal craniofacial growth. AIM: To compare airway volumes in patients with mandibular retrognathism with the normal anteroposterior skeletal relationship, thereby assessing the association between cephalometric variables and airway morphology. METHODS: Cone-beam computed tomography volume scans, and lateral cephalograms, 3-dimensional airway volume and cross-sectional areas of 120 healthy children (54 boys and 66 girls mean age 15.19 ± 1.28) which were done for orthodontic assessment were evaluated. The subjects were divided into 2 groups based on the angle formed between point A, Nasion and point B (ANB) values and cephalometric variables (such as anterior and posterior facial height, gonial angle etc.) airway volumes, and cross-sectional measurements were compared using independent t tests. Pearson’s correlation coefficient test was used to detect any relationship of different parts of the airway and between airway volume and 2-dimensional cephalometric variables. RESULTS: Means and standard deviations for cephalometric, cross-sectional, and volumetric variables were compared. ANB, mandibular body length and facial convexity were statistically highly significant (P < 0.01) whereas condylion to point A, nasal airway and total airway volume (P < 0.05) were statistically significant. The nasal airway volume and the superior pharyngeal airway volume had a positive correlation (P < 0.01), nasal airway was correlated to middle (P < 0.05) and total airway superior had a relation with middle (P < 0.05), inferior and total airway (P < 0.05), middle was related to all other airways; inferior was also related to all the airways except nasal. Lateral cephalometric values were positively correlated with the airway volume with Frankfurt Mandibular Plane Angle and facial convexity showed significant correlations with total airway volume (P < 0.05). Additionally, ANB angle was significantly correlated with total airway volume and superior airway (P < 0.05). CONCLUSION: The mean total airway volume in patients with retrognathic mandible was significantly smaller than that of patients with a normal mandible.